Chlamydia trachomatis Inhibits Homologous Recombination Repair of DNA Breaks by Interfering with PP2A Signaling - Yang Mi (American Society for Microbiology, 2018)
ABSTRACT Cervical and ovarian cancers exhibit characteristic mutational signatures that are reminiscent of mutational processes, including defective homologous recombination (HR) repair. How these mutational processes are initiated during carcinogenesis is largely unclear. Chlamydia trachomatis infections are epidemiologically associated with cervical and ovarian cancers. Previously, we showed that C. trachomatis induces DNA double-strand breaks (DSBs) but suppresses Ataxia-telangiectasia mutated (ATM) activation and cell cycle checkpoints. The mechanisms by which ATM regulation is modulated and its consequences for the repair pathway in C. trachomatis-infected cells remain unknown. Here, we found that Chlamydia bacteria interfere with the usual response of PP2A to DSBs. As a result, PP2A activity remains high, as the level of inhibitory phosphorylation at Y307 remains unchanged following C. trachomatis-induced DSBs. Protein-protein interaction analysis revealed that C. trachomatis facilitates persistent interactions of PP2A with ATM, thus suppressing ATM activation. This correlated with a remarkable lack of homologous recombination (HR) repair in C. trachomatis-infected cells. Chemical inhibition of PP2A activity in infected cells released ATM from PP2A, resulting in ATM phosphorylation. Activated ATM was then recruited to DSBs and initiated downstream signaling, including phosphorylation of MRE11 and NBS1 and checkpoint kinase 2 (Chk2)-mediated activation of the G2/M cell cycle checkpoint in C. trachomatis-infected cells. Further, PP2A inhibition led to the restoration of C. trachomatis-suppressed HR DNA repair function. Taking the data together, this study revealed that C. trachomatis modulates PP2A signaling to suppress ATM activation to prevent cell cycle arrest, thus contributing to a deficient high-fidelity HR pathway and a conducive environment for mutagenesis. IMPORTANCE Chlamydia trachomatis induces DNA double-strand breaks in host cells but simultaneously inhibits proper DNA damage response and repair mechanisms. This may render host cells prone to loss of genetic integrity and transformation. Here we show that C. trachomatis prevents activation of the key DNA damage response mediator ATM by preventing the release from PP2A, leading to a complete absence of homologous recombination repair in host cells.